Association between indoor formaldehyde exposure and asthma: A systematic review and meta‐analysis of observational studies. (19th March 2020) - Yu, Linling; Wang, Bin; Cheng, Man; Yang, Meng; Gan, Shiming; Fan, Lieyang; Wang, Dongming; Chen, Weihong
Abstract: About 339 million people worldwide are suffering from asthma. We aimed to investigate whether exposure to formaldehyde (FA) is associated with asthma, which could provide clues for preventive and mitigation actions. This article provides a systematic review and meta‐analysis of observational studies to assess the association between indoor FA exposure and the risk of asthma in children and adults. An electronic search of PubMed, Embase, and Web of Science was performed to collect all relevant studies published before January 1, 2020, and a total of 13 papers were included in this meta‐analysis. A random‐effect model was conducted to calculate the pooled odds ratio (OR) between FA exposure and asthma. We found that each 10 µg/m 3 increase in FA exposure was significantly associated with a 10% increase in the risk of asthma in children (OR = 1.10, 95% confidence interval = 1.00‐1.21). We sorted the FA concentrations reported in the selected articles and categorized exposure variables into low (FA ≤ 22.5 µg/m 3 ) and high exposure (FA > 22.5 µg/m 3 ) according to the median concentration of FA. In the high‐exposure adult group, FA exposure may also be associated with an increased risk of asthma (OR = 1.81, 95% CI = 1.18‐2.78).